SpeechToast: Augmenting Notifications with Speech Input Focus - Brush, A.J.; Johns, Paul (AVI 2012, 2012)
To explore the value of speech input focus for handling notifications, we built and deployed SpeechToast, an Outlook Add-in that replaces standard email notifications with a version that includes speech input commands (e.g. “open”, “delete”). Notifications shown by SpeechToast have speech input focus when the audio context surrounding the computer is favorable for speech recognition. We deployed SpeechToast to 18 current users of email notifications for 4 weeks. Overall, speech input focus appealed to some participants, while non-users indicated their willingness to have it enabled as long as it did not detract from their experience. Our research suggests that selectively enabling speech input focus could provide natural and intuitive interactions that complement other input modalities.